Improvement of photochemical and enzyme inhibition properties of new BODIPY compound by conjugation with cisplatin - Karanlik, Ceren Can; Karanlik, Gurkan; Taslimi, Parham; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
In this study, new BODIPY complexes were synthesized, characterized and investigated for their some metabolic enzyme inhibition and photophysicochemical properties. BODIPY central core unit was synthesized by using conventional method followed by Suzuki-Miyaura Cross-Coupling reaction. After converting the obtained compound into the diiodinated derivative in the presence of HIO3/I2, quaternization of BODIPY derivative was achieved with cisplatin [cis-PtCl(NO3)(NH3)2] over the pyridine segment. Characterizations of all intermediates and the target compound were determined by 1H-NMR, 13C-NMR and MS spectroscopic methods. The potentials of the synthesized compounds in photodynamic therapy applications were determined by calculating the fluo-rescence, singlet oxygen and photodegradation quantum yields. Also, all complexes were screened for human carbonic anhydrase I, II (hCAs I and II), acetylcholinesterase (AChE), butyryl cholinesterase (BChE), and alpha-glucosidase inhibitory activities. Results indicated that all the synthesized complexes exhibited potent inhib-itory activities against standard inhibitors, revealed by IC50 values.
Keywords: BODIPY; Cisplatin; Singlet oxygen; Cholinesterases; a-Glucosidase; Enzyme inhibition; PHOTODYNAMIC THERAPY; DYES; SERIES; Chemistry; Crystallography